(untitled) (Global Journal of Medical Research, 2018)
Introduction: Trichomonas vaginalis is an anaerobic, flagellated protozoan parasite and the causative agent of Trichomoniasis. It is the most common pathogenic protozoan infection of humans in industrialized countries. Infection rates between men and women are similar with women being symptomatic, while infections in men are usually asymptomatic. Transmission usually occurs via direct, skin-toskin contact with an infected individual, most often through vaginal intercourse. The WHO has estimated that 160 million cases of infection are acquired annually worldwide. Justification: Trichomonas vaginalis infection may lead to serious complications, then early detection may prevent this complications. Objectives: To know the percentage of T. vaginalis infection among the selected group Material and Methods: Descriptive, cross sectional study, used urine specimens to diagnose T. vaginalis infection among selected group of Sudanese women. Result: 1.6% were infected with T. vaginalis. Discussion: The prevalence of Trichomoniasis among the study group is the lowest one in comparison to the previous studies. Conclusion: Many factors may lead to tat lowest result such as, type of the specimen, small sample size and Religion. Acknowledgement: I would like to thanks all the staff of microbiology and parasitology department at soba university hospital for their professional work and kind dealing to the patients and researchers.